(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
In the performance of Khorezm maqams, we observe a separate school of performance, which has special styles and forms, differs from "Shashmaqom" in terms of method and rhythm. In their time, great representatives of the Khorezm school of performance grew up. Among them are such great artists as Muhammad Yaqub Devan, Baba Bulomon, Kamil Khorazmi, Muhammad Yusuf Bayani, Kurji ata, Polli Dozchi, Muhammad Rasul Mirza, Khudoibergan Muhrkan, Muhammad Yusuf Devon-Chokar, Matpano Khudoiberganov, Madrahim Sherozi, Khojikhan Boltaev, Kamiljon Otaniyozov.